Unveiled feather microcosm: feather microbiota of passerine birds is closely associated with host species identity and bacteriocin-producing bacteria - Javůrková, Veronika Gvoždíková; Kreisinger, Jakub; Procházka, Petr; Požgayová, Milica; Ševčíková, Kateřina; Brlík, Vojtěch; Adamík, Peter; Heneberg, Petr; Porkert, Jiří (The ISME journal, 2019)
The functional relevance of microbiota is a key aspect for understanding host-microbiota interactions. Mammalian skin harbours a complex consortium of beneficial microorganisms known to provide health and immune-boosting advantages. As yet, however, little is known about functional microbial communities on avian feathers, including their co-evolution with the host and factors determining feather microbiota (FM) diversity. Using 16S rRNA profiling, we investigated how host species identity, phylogeny and geographic origin determine FM in free-living passerine birds. Moreover, we estimated the relative abundance of bacteriocin-producing bacteria (BPB) and keratinolytic feather damaging bacteria (FDB) and evaluated the ability of BPB to affect FM diversity and relative abundance of FDB. Host species identity was associated with feather bacterial communities more strongly than host geographic origin. FM functional properties differed in terms of estimated BPB and FDB relative abundance, with both showing interspecific variation. FM diversity was negatively associated with BPB relative abundance across species, whereas BPB and FDB relative abundance was positively correlated. This study provides the first thorough evaluation of antimicrobial peptides-producing bacterial communities inhabiting the feather integument, including their likely potential to mediate niche-competition and to be associated with functional species-specific feather microbiota in avian hosts.
Keywords: Animals; Feathers; Birds; Bacteriocins; druhová specificita; RNA, Ribosomal, 16S; Microbiota; Species Specificity; ptáci; Host Specificity; Phylogeny; mikrobiota; peří; Bacteria; bakteriociny; zvířata; fylogeneze; RNA ribozomální 16S; hostitelská specificita